Mortes possíveis : análise de manifestações da morte no cinema documentário ocidental - Lago, Tainah Morais (2016)
This research consists of a study about the manifestations of death on four films of the western documentary cinema: Les Maîtres Fous (1954), directed by Jean Rouch; Mondo Cane e Mondo Cane 2 (1962 e 1964), directed by Gualtiero Jacopetti e Franco Prosperi; e Nick’s Film: Lightning Over Water (1981), directed by Wim Wenders e Nicholas Ray. The filmic works here selected show different angles of mortality, approaching issues that go from the death of another person, marked by cultural otherness in relation to the filmaker, to the death inserted in a familiar context to the filmakers themselves. The exam undertaken about the set of movies is based in two fundamental elements in the filed of this cinematographic genre: the first is the insertion of the work in an ethical space sanctioned by society, the second refers to the indexation of the movie content as an assertive. The visual manifestation of death documented points to space constituted of concrete social relations that build up an appropriate basis, proportioning the questioning of moral order to the acts of producing and/or watching such images. It is important to clarify that the visual representation of death is produced through two elements: violence - practiced against a living body - and the dead body. Both elements are associated to the term when used in this study. The conceptions of death act in the structuring of the livelihood and, from this notion, historical data about the iconography of death in western society are retaken, from medieval ages to the present. The course of this trajectory of men’s confrontation with their own mortality, revealed by the different means of appropriation of the death referring to specific socio-historical groups, allows the perception of today’s notions associated to the issue as a result of a historical construction instead of absolute systematizations. From the principle that anthropology perceives cinema as a cultural product, the manifestations of the intense-image of death in documentary are understood as registers of particularities of our own culture about this matter, constituting an important field for anthropological research.